¿Tomar no tomar?: análisis de los motivos de consumo y no consumo de alcohol en jóvenes (2013)
The study analyzes the reasons for consuming alcohol or not among adolescents in a school in Chia. The study has a content analysis qualitative approach, in which open-ended questions were used. Later on, categories of analysis were created and through a quantitative approach results were assessed. The study was conducted on a sample of 282 adolescents. Results identify the categories and subcategories of consuming reasons, which show the various themes and issues that young people described. The discussion highlights the importance of developing prevention programs that take into account the reasons young people have to use or not consume alcohol. These programs should attend to individual differences in students, promote personal resources and protective factors that discourage cultural associations with alcohol use in young people.Keywords: adolescence, alcohol consumption, reasons for consumption, reasons for non consumption, prevention.